E-Warung Mobile: Inovasi UI/UX untuk Mendorong Digitalisasi Usaha Kecil - Adhitya Putra Arif Nugroho; Fareza Maulana A.P; Luhtitisari Luhtitisari; Fajar Mahardika (Universitas Ma Chung, 2026)
Digital transformation in the small business sector, particularly traditional warung (small retail shops), has become an urgent necessity amid the rapid advancement of information technology. However, low levels of digital literacy and limited access to user-friendly applications remain significant barriers to technology adoption. This study aims to design and evaluate the quality of the User Interface (UI) and User Experience (UX) of the E-Warung Mobile application as an effort to support the digitalization of small businesses. The research method employed is a design thinking approach, which consists of the stages of empathize, define, ideate, prototype, and testing. User experience evaluation was conducted using the User Experience Questionnaire (UEQ), which measures six main aspects: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. Data were collected through questionnaires distributed to 25 respondents who are small business owners or prospective users, after they completed a series of task scenarios using the application prototype. The analysis results indicate that the mean scores for each UEQ aspect are as follows: Attractiveness (1.75), Perspicuity (1.68), Efficiency (1.72), Dependability (1.65), Stimulation (1.80), and Novelty (1.60) on a scale ranging from -3 to +3. Based on the UEQ benchmark, all aspects fall within the “above average” to “good” categories, indicating that the application demonstrates high usability, is easy to understand, efficient, and capable of delivering a positive user experience. In conclusion, this study shows that the implementation of user-centered UI/UX design, quantitatively evaluated using UEQ, can enhance the quality of user interaction and has the potential to promote broader adoption of digital technology among small businesses